The Use of VOA to Improve the Listening Skills of the First Semester Students of English Education Program of STKIP Kie Raha Ternate - S Syamsia (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2023)
This research aimed to investigate whether or not the students’ listening skills can be developed through VOA. Based on the result of the teaching and learning process especially in the listening subject, The researcher found that many students still had difficulty recognizing the sound of words, the meaning, and the content in English when hearing the spoken version. These indicate that the student's ability in listening comprehension is still low. The population in this study was all students of the English Department Program. They are 53 students who registered for the 2022/2023 academic years. The sample was taken from first-semester students, they are 13 Students. To collect the data, the researcher used a test. Based on the findings and discussion, the researcher concludes that: The data show that the students' listening effectiveness before and after the treatments is a significant difference. It was found in the students' post-test was higher than the pre-test, which proved that the use of VOA in teaching listening skills contributed to the students' being more effective in listening to English. And using VOA can improve the students' listening ability even though the results of them are different. It can be seen through their increasing score from pre-test to post-test.